2016
DOI: 10.1108/ec-11-2014-0228
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid vibration and rest-to-rest control of a two-link flexible robotic arm using H∞ loop-shaping control design

Abstract: Purpose This study presents a method for simultaneous motion and vibration control of light-weight slender robotic arms, known as flexible manipulators. In this paper, a new control algorithm is proposed for a two-link manipulator with elastic links. Design/methodology/approach The controller includes a MIMO H∞ Loop-Shaping Design (H∞LSD) as the feedback controller, and a command pre-shaping filter as the feed-forward controller. The conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Commonly, in the FE models which were used for FLM modelbased control design, each link is modelled with one FE beam element. Sayahkarajy et al 55 proposed modelling of TLFMs using high-resolution FE meshes followed by a modal-order reduction. They proposed a robust control algorithm for rest-to-rest manoeuvring and vibration control of the TLFM.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…Commonly, in the FE models which were used for FLM modelbased control design, each link is modelled with one FE beam element. Sayahkarajy et al 55 proposed modelling of TLFMs using high-resolution FE meshes followed by a modal-order reduction. They proposed a robust control algorithm for rest-to-rest manoeuvring and vibration control of the TLFM.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…Adaptive control can also solve the control problem of systems with uncertainties [6], [7]. H-inf control is widely used in the control problem of this kind of flexible system with uncertainty [8], [9], [10]. For the widely existing flexible system with weak damping, because it is more convenient to use coprime factor perturbations to describe this system so the H-inf loop forming method based on coprime factor perturbations is often used for weakly damped flexible system.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly to ensure stability and peformance objectives regardless of bounded difference between nominal plant and actual plant. In the past, Hilel et al (1992), and more recently, Sayahkarajy et al (2016), have demonstrated that H loop shaping-based design is an attractive approach to achieve robust tracking performance in presence of external disturbances. It is also an excellent control technique to design decoupled control system as it relies on a two-step precedure; that is, firstly, the plant is shaped to the desired frequency spectrum and then the controller is designed to minimize the worst closed-loop gain for disturbance rejection after selecting appropriate performance weights.…”
Section: Introductionmentioning
confidence: 99%